PENGARUH FAKTOR-FAKTOR EKONOMI MAKRO TERHADAP RETURN SAHAM DI PASAR MODAL INDONESIA DENGAN PENDEKATAN ARBITRAGE PRICING THEORY PERIODE TAHUN 2008-2010 - Wawan Ichwanudin (Indonesian Journal of Economics and Business, 2012)
The most common problem with investing in the stock market is the uncertainty of the stock prices. In order to minimize this uncertainty, financial experts have developed various models, one of which is the Arbitrage Pricing Theory (APT). This theory can be used to predict the expected return.The purpose of this study is to formulate an APT model in Indonesia. Pre-specified macroeconomic factor approach is used to formulate this APT model. The determined macroeconomic factors include inflation, SBI interest rate, money supply, exchange rate, and oil price. The sample of this study is a number of stocks that meet certain criteria. This study took place from 2008 to 2010.This study uses secondary data and two-stage regression analysis method. The APT model result from second step regression with backward regression approach by f-test and t-test. Based on the data analysis, it can be concluded that inflation risk, exchange rate risk and surprise oil price risk are risk factors in the Indonesian Stock Exchange. This study produces an APT model that consists of three factors: inflation, Rupiah exchange rate to US Dollar, and oil price.